PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN DAN PERSEPSI KEAMANAN TERHADAP KEPUTUSAN PENGGUNAAN OVO PT VISIONET DATA INTERNASIONAL (STUDI PADA PENGGUNA OVO DI KOTA SURAKARTA) - Ahmad Iliyin; Widiartanto Widiartanto (Universitas Diponegoro, 2020)
Increasing competition for e-money, one payment service that is growing rapidly is OVO, an online payment service providers based application. The amount of OVO users has been decreased although target achievement increased in its realization but in the percentage of changes there has been a sharp decline. The type of research using explanatory research with data collecting technics by interview and data collection tools used offline and online questionnaires. The methods of this study is purposive sampling with a sample of 100 respondents. Data analysis technique in this study using validity test, reliability test, simple linear regression, multiple linear regression, t-test, and F- test with SPSS 25.0. The result of research indicate that variable perceived ease of use is positive effect of decision to use OVO in Surakarta city. Variable Peceived security is positive effect of decision to use OVO in Surakarta city. Variable preceived ease of use and variable preceived security significantly is positive effect of decision to use OVO in Surakarta city. Based on the results of the study, the researcher suggested that Visionet data internasional company can assure its users of user data in OVO application that it has secured its confidentiality, so that users do not worry about excessive amounts, and supports OVO providing education for use using OVO interest in decisions using OVO.